Clinical activity of sunitinib rechallenge in metastatic renal cell carcinoma—Results of the REchallenge with SUnitinib in MEtastatic RCC (RESUME) Study. (July 2016) - Oudard, Stéphane; Geoffrois, Lionnel; Guillot, Aline; Chevreau, Christine; Deville, Jean-Laurent; Falkowski, Sabrina; Boyle, Helen; Baciuchka, Marjorie; Gimel, Pierre; Laguerre, Brigitte; Laramas, Mathieu; Pfister, Christian; et al.
Abstract: Aim: To assess the efficacy and tolerability of sunitinib rechallenge in the third-line or later setting in patients with metastatic renal cell carcinoma (mRCC). Patients and methods: This observational study comprised 61 mRCC patients at 19 centres in France who received sunitinib rechallenge between January 2006 and May 2013. Patients received first-line sunitinib, ≥1 different targeted therapies, and then sunitinib rechallenge. Patient/disease characteristics, tolerability, treatment modalities, and outcomes of therapeutic lines were recorded. The primary end-point was progression-free survival (PFS) in sunitinib rechallenge. Results: Analyses included 52 patients; median age was 59 years, 75% were male, and 98% had clear-cell mRCC and prior nephrectomy. At sunitinib rechallenge versus first-line, patients had poorer performance (Karnofsky performance status 90–100: 30% versus 81%) and Memorial Sloan Kettering Cancer Centre prognostic risk (poor risk: 18% versus 3%). Overall, 20%, 65%, 12%, and 4% received sunitinib rechallenge as third-, fourth-, fifth-, and sixth-line therapy, respectively, at 14.6 months (median) after stopping initial treatment. With first-line sunitinib and rechallenge, median PFS was 18.4 and 7.9 months, respectively; objective response rate was 54% and 15%. Two of eight rechallenge responders had not achieved first-line response. Median overall survival was 55.9 months. The sunitinib rechallenge safety profile was as expected, with no new adverse events reported. Conclusions: Sunitinib rechallenge is a feasible treatment option with potential clinical benefit for mRCC patients. Disease progression with first-line sunitinib may not be associated with complete or irreversible resistance to therapy. Highlights: Sunitinib rechallenge in metastatic renal cell carcinoma patients was assessed. Median PFS was 18.4 and 7.9 months with first-line sunitinib and rechallenge. Sunitinib rechallenge safety was as expected with no new adverse events reported. Sunitinib rechallenge is feasible with potential clinical benefit. Initial progression with sunitinib may not be associated with absolute resistance.